Glycans and Glycan-Binding Proteins in Atherosclerosis - Eckardt, Veit; Weber, Christian; von Hundelshausen, Philipp (Thrombosis and Haemostasis, 2019)
Complex glycans are readily accessible on the endothelium and on cell and plasma components. They interact with glycan-binding proteins which translate their structure into function. Advanced analytical tools are available to investigate their structure and functional interactions. Modifications to glycan structures which alter their capacity to bind proteins are particularly relevant in atherosclerosis. We summarize the regulatory role of glycans and their binding partners in the development of the disease. Given their complexity, accessibility, and important functional role, glycans and glycan-binding proteins represent promising diagnostic tools and therapeutic targets.
Keywords: glycocalyx; glycosaminoglycan; chemokine; selectin; galectin; low-density lipoprotein